Evaluating Appropriateness of Speech Act of Criticizing by Indonesian EFL Learners: A Pragmatic Comprehension Study - Devi Pratama Putri; Agus Wijayanto; Endang Fauziati (STAI Hubbulwathan Duri, 2023)
Adequate pragmatic competence, or the ability to use language in a social context appropriately, is essential for successful communication, particularly across cultures and societies. Many previous studies in appropriateness focused on speech act production, pragmatic development, and rater evaluations, but only a few investigated pragmatic comprehension. Therefore, this current research attempts to investigate EFL learners' comprehension of the appropriateness of criticism speech acts and the foundation that EFL learners consider in evaluating appropriateness. This study involved 20 EFL learners as participants. The study used a questionnaire with DCTs and open-ended questions to elicit the data. The findings revealed that EFL learners could understand the appropriateness of criticism speech acts They could indicate which utterances were associated with appropriateness or inappropriateness by considering various criteria such as politeness, power and social distance, linguistic forms, strategies, intentions, reasoning, and settings. This research has implications for English learning in that teachers should promote appropriateness as an important aspect of pragmatic competence to EFL learners so that they can use language appropriately to communicate in the target language.